Effects of Walking on Fatigue in Cancer Patients: A Systematic Review and Meta-analysis. Issue 1 (January 2022) - Wang, Pengcheng; Wang, Di; Meng, Aifeng; Zhi, Xiaoxu; Zhu, Ping; Lu, Lijing; Tang, Lin; Pu, Yalou; Li, Xiaoli
Abstract : Background: Walking is a simple form of exercise that is easily accepted by patients. Exercise is one of the main ways to control cancer-related fatigue (CRF). However, there are conflicting data on the association between walking and severity of CRF. Objective: The aim of this study was to assess the overall effect of walking on CRF among adult cancer patients. Methods: Databases including PubMed, CINAHL, EMBASE, and Cochrane Library were systematically reviewed to identify suitable randomized controlled trials from inception to February 29, 2020. Two reviewers independently evaluated the risk of bias and extracted correlated data with Cochrane Handbook of Systematic Reviews on Interventions. The data analysis was performed by Review Manager 5.3. Results: A total of 12 studies with 1064 patients were identified. Integrated result analysis of walking yielded a statistically significant effect on CRF (standard mean difference [SMD], −0.66; 95% confidence interval [CI], −1.06 to −0.26). Subgroup analysis demonstrated that intervention time longer than 6 weeks (SMD, −0.89; 95% CI, −1.22 to −0.57) had a better effect on fatigue compared with that of less than 6 weeks (SMD, 0.03; 95% CI, −0.39 to 0.45). The study showed walking was statistically more effective than the control intervention in patients undergoing cancer treatment (SMD, −0.79; 95% CI, −1.16 to −0.42). Descriptive analysis also showed that walking was effective for cancer patients who completed treatment. Conclusions: Walking is effective for CRF during and after cancer therapy. Implications for Practice: The results provide evidence for a general exercise form to relieve fatigue in cancer patients and facilitate support for future clinical trials and work.